2011
DOI: 10.1111/j.1365-2648.2011.05785.x
|View full text |Cite
|
Sign up to set email alerts
|

Do assistive devices, training, and workload affect injury incidence? Prevention efforts by nursing homes and back injuries among nursing assistants

Abstract: Aims This paper is a report of a study of association between workplace injuries experienced by nursing assistants in nursing homes in the United States and four factors that may affect injury rates: initial nursing assistant training, training at the current facility, lifting devices, and time to execute daily duties. Background High injury rates among nursing personnel have been reported in multiple settings across countries. The existing literature is divided on the effectiveness of training and assistive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 22 publications
2
47
0
1
Order By: Relevance
“…Each year, more than 10,000 nurses in the United States experience work-related musculoskeletal disorders resulting in lost work days and nurses rank among the top five occupations for musculoskeletal disorders (Bureau of Labor Statistics, 2010). Injuries from patient handling tasks account for 31-66% of all musculoskeletal injuries among healthcare workers (D'Arcy et al, 2012;Kim et al, 2012;Pompeii et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Each year, more than 10,000 nurses in the United States experience work-related musculoskeletal disorders resulting in lost work days and nurses rank among the top five occupations for musculoskeletal disorders (Bureau of Labor Statistics, 2010). Injuries from patient handling tasks account for 31-66% of all musculoskeletal injuries among healthcare workers (D'Arcy et al, 2012;Kim et al, 2012;Pompeii et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Aids and equipment used to reduce physical demands of the PTs work include: height-adjustable beds, lifting belts, slide boards, splints, and stools on casters ("wheelie stools") [28]. Lately, lifts and sliding sheets have been highly recommended [29]. Cromie et al [15] have defined "self-protective behaviors" as outsourcing, preventive or reactive strategies.…”
Section: Impacts Responses and Prevention Strategiesmentioning
confidence: 99%
“…It is confirmed that the injuries to the osteoarticular apparatus (particularly limbs) predominantly strike male workers performing moderate to heavy manual tasks, often employed in traditionally risky industrial sectors (construction, metal industry) (2,12). Interestingly, an appreciable fraction (almost 10%) of the accidents involved health workers: the risk of musculoskeletal injuries for nurses and other healthcare personnel has been underscored by several authors (13,14). As expected, the personalized rehabilitative program was beneficial, as indicated by pain reduction and improvement of function.…”
Section: Discussionmentioning
confidence: 75%